Peran Guru dalam Mewujudkan Budaya 5S melalui Penerapan Hidden Curriculum di SDN Lidah Wetan II - Darmawan, Diki; Bani, Malista Sint Oida; Janah, Eliya Uslifatul; Lutfiani, Deyah Nur Alfi (utile: Jurnal Kependidikan, 2023)
Abstract: Hidden curriculum includes values, norms and behaviors that are not overtly taught, but are indirectly understood and adopted by individuals through daily experiences in the educational environment. The role of hidden curriculum is very important in undergoing educational programs, although it actually appears as a result of unplanned things or natural experiences of students. One of the manifestations of the hidden curriculum is the 5S culture (smile, greeting, greeting, politeness and courtesy). The implementation of hidden curriculum through the 5S culture can help in the development of student character. The purpose of this study was to determine the role of teachers in implementing the hidden curriculum regarding 5S in the classroom as well as the implementation of 5S by students. This research uses a qualitative approach with data collection methods using interviews with several classroom teachers. Based on the results of the research conducted, teachers have a very important role in implementing the hidden curriculum. Teachers at SDN Lidah Wetan II have implemented the hidden curriculum, especially those related to 5S well, this can be seen from most students have implemented the 5S culture at school. Hidden curriculum has an important role in the development of student character at SDN Lidah Wetan II, namely guiding students, increasing student motivation, making student behavior better, polite, disciplined, berahklaqul karimah, and students become more capable, skilled, independent and character.